Fast Fashion: Fast Sewing, Fast Selling, Fast Throwing Away - ГуроваОльга Юрьевна (Journal of Economic Sociology, 2010)
The article dwells on the phenomenon of ‘fast fashion’, the new understanding of fashion which superseded theconcepts of class and mass fashion. The concept of ‘fast fashion’ views fashion in the context of global industry anddivision of labour in the world economy, which leaves production and distribution of goods for developing, ‘thirdworld’, countries, whereas marketing and consumption are mostly performed in capitalist countries. The articledemonstrates the ways in which the concept of fast fashion glimpses in consumption practices of citizen of Saint-Petersburg via document and quantitative analyses of data from the survey held in Saint-Petersburg in 2007.